Drawn to 360°: How can the aesthetics and qualities of traditional 2D animation storytelling add to the immersive VR projection paradigm?. Issue 1 (1st December 2018) - Young, Millie
The discussion will explore the aesthetic of hand drawn animation and the qualities this brings to the animation story through the analysis of selected practitioners in the field who bring drawn qualities that (could) crossover into 360°. Through the analysis the discussion will demonstrate the convergence of narrative structures and strategies from conventional animation and film narrative theory that are commonly present, applied or adapted within the emerging film syntax and grammar for VR. The article will go on to discuss how these theories and strategies might aid approaches to creative practitioners to enhance the possibilities for immersive storytelling by utilizing the hand drawn aesthetic in storytelling for the VR/360° world. First, to open the discussion, there is a question of the immersion experience and aesthetics present in the emerging media for 360° and VR and aspects of the whole immersive experience that are opening up for artists and audiences.